Greening Muhammadiyah: Waste Charity Movement as Preliminary Initiatives for Addressing the Triple Planetary Crises - David Efendi; Arifin M Ade; Purwo Santoso; Ulil Amri (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
Amid the threat of a triple planetary crisis (climate change, pollution, and biodiversity loss), the Waste Charity Movement (Gerakan Sedekah Sampah or GSS), initiated by Muhammadiyah, can be considered the praxis of liberation ecotheology under banner green Islam. Developed collectively, it responds to this crisis while promoting social-religious responsibility and economic solidarity. This article demonstrates how Muhammadiyah’s GSS as preliminary initiative actively advances waste management in Indonesia. Drawing on discourse analysis of Muhammadiyah affiliated media, this study illuminates the involvement of Islamic organizations in waste charity initiatives. It offers two key implications: theoretically, it highlights Muhammadiyah’s contribution to addressing planetary crises through education and empowerment within waste charity; practically, it proposes a novel pedagogical approach to mitigating these crises.